Effects of continuous ethinylestradiol and drospirenone administration on body mass and mammary gland in female mice fed a standard or high-fat diet - Aguiar , Gésily de Souza; Chaves (In Memorian), Janaína de Oliveira; Freitas, Israelle Netto; Oliveira, Kênia Moreno de; Silva, Ana Beatriz Barbosa da; Silva, Stefanny Calixto da; Ribeiro , Rosane Aparecida; Nara Henriques Blanc, Helene (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2025)
Combined oral contraception (COC) is used by millions of women worldwide, but some studies suggest it may increase the risk of breast cancer. Overweight and obesity have reached epidemic levels and are also risk factors for mammary gland neoplasms. This study evaluated the effects of a COC containing ethinylestradiol (EE2) and drospirenone (DRSP) on reproductive organs, particularly the histopathology of inguinal mammary glands in reproductively active female mice fed a standard diet (SD) or high-fat diet (HFD). Adult Swiss female mice received either SD or HFD and were treated daily by gavage with distilled water [control (CTL)-SD and CTL-HFD] or 0.6 µg EE2 and 60 µg DRSP (COC-SD and COC-HFD) for 65 days. COC treatment disrupted the estrous cycle, with vaginal smears showing fewer squamous cornified cells but more leukocytes, deep cells, and mucus, characteristic of metestrus and proestrus. At the end of the experiment, COC-SD females showed body weight (BW), inguinal white adipose tissue (WAT) mass, and uterus and ovary weights similar to CTL-SD. HFD increased BW and WAT mass without altering uterus and ovary weights. COC reduced HFD-induced BW and WAT gain but increased uterus weight in COC-HFD females. Morphological analysis of mammary glands revealed no pathological signs or structural changes in acini, ducts, or lumens due to COC or diet. Notably, COC-HFD females had smaller white adipocytes than CTL-HFD, while beige adipocyte levels remained unchanged across groups. These findings suggest that EE2 and DRSP may regulate HFD-induced obesity without adversely affecting mammary gland morphology.